Closed Bipolar Electrode Array for Optical Reporting Reaction‐Coupled Electrochemical Sensing and Imaging. Issue 8 (8th December 2022) - Qin, Xiang; Gao, Jiao; Jin, Hua‐Jiang; Li, Zhong‐Qiu; Xia, Xing‐Hua
Abstract: This review centers on a closed bipolar electrode (BPE) array using an electro‐fluorochromism (EFC) or electro‐chemiluminescence (ECL) reaction as the reporting reaction. Electrochemical signals at one pole of the closed BPE array can be transduced into the EFC or ECL signals at the opposite pole. Therefore, the current signal of a redox reaction can be easily detected and imaged by monitoring the luminescence signal. Recent developments in closed BPE array‐based EFC and ECL sensing and imaging are summarized and discussed in detail. Finally, we consider the challenges and opportunities for improving the spatial resolution of closed BPE array‐based electrochemical imaging, and emphasize the important application of this technique to the imaging of cellular activities at the single‐cell level. Abstract : Powerful sensing and imaging abilities : This review highlights the recent advances in closed bipolar electrode (BPE) arrays using an electro‐fluorochromism (EFC) or electro‐chemiluminescence (ECL) reaction as the reporting reaction to realize sensing and imaging. It demonstrates the advantages of a closed BPE array, such as the physical separation of two poles, the independence of each electrode, and the simplicity and controllability of the system.